Associations between self-harm and distinct types of impulsivity. (April 2017) - Chamberlain, Samuel R.; Redden, Sarah A.; Grant, Jon E.
Abstract: Objective: There is an ongoing debate regarding how self-harm should be classified. The aim of this study was to characterize associations between self-harm and impulsivity. Method: Total 333 adults (mean [SD] age 22.6 (3.6) years, 61% male) were recruited from the general community. History of self-harm was quantified using the Self-Harm Inventory (SHI), which asks about 22 self-harm behaviors. Principal components analysis was used to identify latent dimensions of self-harming behaviors. Relationships between self-harm dimensions and other measures were characterized using ordinary least squares regression. Results: Principal Components Analysis yielded a three factor solution, corresponding to self-injurious self-harm (e.g. cutting, overdoses, burning), interpersonal related self-harm (e.g. engaging in emotionally or sexually abusive relationships), and reckless self-harm (e.g. losing one's job deliberately, driving recklessly, abusing alcohol). Regression modelling showed that all three dimensions of self-harm were associated with lower quality of life. Conclusions: This study suggests the existence of three distinct subtypes or 'latent factors' of self-harm: all three appear clinically important in that they are linked with worse quality of life. Clinicians should screen for impulse control disorders in people with self-harm, especially when it is self-injurious or involves interpersonal harm. Highlights: Self-harm was common in our sample, and people with self-harm showed low quality of life. Significant factors associated with self-harm were higher nicotine consumption, presence of an impulse control disorder, and higher dimensional ADHD symptoms. Self-harm was not associated with cognitive dysfunction or personality-related measures of impulsivity.